I know the method and can solve other initial value problems. This is the question given: dy/dx + y(-2) Sin(3x) = 0 for t > 0, with y(0) = 2. I've brought the dy/dx and let it equal to the rest of the expression so it is now: dy/dx = -y-2 Sin(3x) , with y(0) = 2 (i.e. when x = 0, y = 2 ) The -y-2 is obstructing me from integrating both sides and solving for constant C using the information given. What would I have to do to eliminate the -y-2 entirely from the question so I can continue standard procedures?